Experience of applying azelaic acid in dermatology - Y. S. Kondratyeva; O. A. Kokina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents current published data on 30 years of experience in applying of azelaic acid in dermatology. Data on pharmacokinetics, efficacy and safety in the international practice; results of study and therapeutic efficacy of different dosage forms are presented.